PENDAMPINGAN DAN PELATIHAN MANAJEMEN PUBLIKASI PENELITIAN DAN PENGABDIAN BERBASIS OPEN JOURNAL SYSTEM DI AKADEMI MILITER MAGELANG - Silitonga, Frangky; Dwi Joko Siswanto; Natalina Kristiani; Aryananta Lufti; M. Baidlowi; Agung Prapsetyo; Tjatur Supriyono (PPM Sdirjianbang Akademi Militer, 2023)
In this OJS management mentoring and training activity at the Akademi Militer Magelang (Akmil) as a collaborative service activity between the Politeknik Pariwisata Batam and the Akmil. The target achievement of this activity is able to create a means of publishing scientific papers from the results of OJS-based research and service. This journal uses the V.3.3 type of PKP. So far the Military Academy itself has had a journal to publish the results of research and dedication of lecturers and students in printed form since 2011. Where the means of publication from 2011 to mid-2022 are Jurnal Teknik Sipil Pertahanan, Elektrosista, Mekanikasista, Mahatvavirya, Tidar Bakti, Adhitakarya Akademi Militer, Dwija Kusuma, Bunga Rampai Akademi Militer and Prosiding Seminar Nasional Akademi Militer. All of these journals which are means of publication are the objects of community service activities through mentoring and training. In this activity, the servant collaborated between the Akmil institution and the Batam Tourism Polytechnic, the method of service activities was carried out online as supported by the use of a live meeting-based information system to accelerate finding solutions and the priority scale of OJS-based publication journals was at Akmil. The method approach used is lectures, role play and demonstrative as well as direct practice in live meetings using zoom meetings that have been scheduled regularly and in a structured manner. The results obtained are participants are able to register at OJS as writers, can submit articles, then become part of the editorial board and can play a role in the regular and measurable OJS management process before the articles are published until the articles will be published by OJS. The limitations of long distances, time and instruments used during mentoring activities for community service activities can be minimized with the support of internet access technology that is quite good, the enthusiasm of the activity participants and a family atmosphere to jointly advance the Akmil in the consistency of research publications and community service using journals based OJS at Akmil. In the end all OJS in Akmil will be accredited in the National Journal Level, even indexed at the international level.